Consolidated Feedback on Tanzania Higher Education University Strategic Investment Plans - Adam, Taskeen; Koomar, Saalim; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk Response provides feedback on 15 Tanzania University Strategic Implementation Plans (USIPs) submitted to the Word Bank’s Higher Education for Economic Transformation Project (HEET). The feedback is intended to enhance and strengthen the plans provided by universities such that the USD 300 million is allocated and spent most effectively.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3986727 2129771:B5Z854HJ 2339240:IEATEWRY 2405685:7AFXFRPC
Keywords: Helpdesk Response; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF; dode_eth-src-eth; dode_eth-trf2-dode

The Maldives and Sri Lanka: Question & Answer Session - Adam, Taskeen; Kaye, Tom; Haßler, Björn (EdTech Hub, 2020)
EdTech Hub participated in a question and answer session in May 2020 for policymakers in The Maldives and Sri Lanka. The session focused on the challenges and issues in designing effective distance education programmes during the Covid-19 pandemic. This document provides answers to a list of 13 questions received from stakeholders.
ZenodoArchiveID: 5652128 previousZenodoArchiveID: 3885817 previousshortDOI: 10/ghgngv previousshortDOI: 10/ghgngv previousDOI: 10.5281/zenodo.3885817 previousshortDOI: 10/ghgngv EdTechHub.Source: 2405685:HE2Q6Z8Y EdTechHub.Source: <this> shortDOI: 10/ghgngv KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3885817 10.53832/edtechhub.0018 10/ghgngv 2129771:YC82FCEP 2339240:TND87RAP 2405685:HE2Q6Z8Y 2405685:SRU74BP6
Keywords: F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Deploying an e-Learning Environment in Zanzibar: A Short Guide - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
In April 2020, the MoEVT and the World Bank approached the EdTech Hub to explore the feasibility of implementing a Virtual Learning Environment (VLE). The parties agreed on three deliverables to support this work. 1. A practical and actionable report analysing key factors to be considered in deploying an e-learning platform in Zanzibar. 2. A report documenting the process of sourcing appropriate digital content, aligning this content with the curriculum and populating the e-learning system accordingly. 3. An implementation plan to guide the deployment of an e-learning system in Zanzibar. This presentation deck is the third deliverable.
ZenodoArchiveID: 4706000 previousDOI: 10.5281/zenodo.4706000 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3971656 10.5281/zenodo.4706000 10.53832/edtechhub.0029 2129771:YZIID28Y 2339240:7P4VDPLY 2339240:WYT4QCIW 2405685:85C5HVC7 2405685:I86XXKMH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Deploying an e-learning Environment in Zanzibar: Digital Content Curation - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
In April 2020, the Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank approached EdTech Hub (the Hub) to explore the feasibility of implementing a Virtual Learning Environment (VLE). The MoEVT, the World Bank and the Hub agreed that the Hub would work with the MoEVT to develop the following 1. A practical and actionable report analysing key factors to be considered in deploying an e-learning platform in Zanzibar. 2. A report documenting the process of sourcing appropriate digital content, aligning this content with the curriculum and populating the e-learning system accordingly. 3. An implementation plan to guide the deployment of the e-learning system. This document addresses the second part of the request and is an elaboration of the digital content selection, curation, and adaptation process suggested in the first report. However, this document is a stand-alone piece that does not require familiarity with any of the other deliverables.
ZenodoArchiveID: 3966976 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3966976 2129771:XMGQ4JQJ 2339240:L5RLM582 2339240:R72E853W 2405685:T2W7MU3K 2405685:U49W6LTF 2405685:ZI8PHKCC
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:v2; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech in Liberia: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652130 previousZenodoArchiveID: 3830953 previousshortDOI: 10/ghgk68 previousDOI: 10.5281/zenodo.3830953 shortDOI: 10/ghgk68 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3830953 10.53832/edtechhub.0033 10/ghgk68 2339240:XCBTX2XL 2405685:2HM2SBVM 2405685:FU7Z8QM7
Keywords: C:Liberia; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH